Increasing Health Cadre Capacity in Education and Counseling Services at Posyandu and Posbindu - Triyanto, Arifin; Subagya, Ami Novianti; Kusumawardhana, Feri Dini; Hendriyanti, Yeni; Septiani, Dila; Jatira'ufani, Nefit Anugrah (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT The health status of Indonesian society both in toddler, adult population and elderly are still a serious concern. Community-based health services such as posyandu and posbindu become an effort to maintaining health in community. Currently, activities such as posyandu and posbindu face many diverse challenges. One of the obstacles experienced is the lack of role of health cadres. Training programs for health cadres can increasing the number of posbindu cadres, increasing the availability of health promotion media for posbindu participants, increasing cadre knowledge and skills in education and counseling. This activity aims to increase the capacity of health cadres in education and counseling services at posyandu and psbindu. The method applied in this community service is through health education. The series of activities include health education through lecture methods and question and answer discussions and at the end of the session a joint screening simulation of non-communicable diseases and counseling simulations were carried out. In this activity, the increase in cadre capacity was evaluated in terms of knowledge with pre- and post-tests. The activity was attended by 20 participants consisting of health cadres at posyandu, posbindu and youth organizations who served as youth cadres. The results of the pre- and post-test measurements showed that there was an increase in participant knowledge by 18 points with a p value of 0.001. Based on these results, it can be concluded that health education activities for cadres can increase the capacity of cadres in education and counseling services at posyandu dan posbindu. Keywords: Education, Health Cadres, Counseling, Posbindu, Posyandu